SOME ASPECTS OF THE RESEARCH IN THE LABORATORY OF THE MUSà‰E DE LA MUSIQUE, PARIS CITà‰ DE LA MUSIQUE - Vaiedelich, Stéphane (Archeomatica, 2013)
Experience The Musée de la Musique has a research and restoration laboratorythat combines applied research dedicated to the study and conservation ofmusical instruments while also providing services linked to the collection. Theactivity of the laboratory falls within the scope of the study of the materialand cultural object represented by the musical instrument and the values itslegacy is leaving.The research conducted there has a concrete application in the conception andimplementation of the conservation choices regarding the Musée's collection:pre-emptive or curative conservation, presentation of works of art as part ofdifferent exhibitions, and obviously the maintenance of their working order.